Enzymatic synthesis of fatty hydrazides from palm oils - Mohamad, Sharifah; Wan Yunus, Wan Md. Zin; Haron, Md. Jelas; Ab Rahman, Mohamad Zaki (Japan Oil Chemists' Society, 2008)
Fatty hydrazides (FH) have been successfully synthesized from palm oils by a one-step lipase catalyzed reaction. The synthesis was carried out by treating the oils with hydrazine hydrate at neutral pH using an immobilized lipase, Lipozyme as the catalyst. The percentages of conversion of RBD (refined, bleached and deodorized) palm oil (PO), RBD palm olein (POn) palm stearin (PS) and RBD palm kernel olein (PKOn) into their fatty hydrazides are 95,97,97 and 99, respectively.